Long‐term outcome in patients with ST segment elevation myocardial infarction and multivessel disease treated with culprit‐only, immediate, or staged multivessel percutaneous revascularization strategies: Insights from the REAL registry. Issue 6 (1st February 2014) - Manari, Antonio; Varani, Elisabetta; Guastaroba, Paolo; Menozzi, Mila; Valgimigli, Marco; Menozzi, Alberto; Magnavacchi, Paolo; Franco, Nicoletta; Marzocchi, Antonio; Casella, Gianni
<x xml:space="preserve">Abstract</x> Objectives To examine the differences in cardiac outcomes for patients with ST‐elevation myocardial infarction (STEMI) and multivessel disease (MVD) as a function of whether they underwent culprit‐only primary percutaneous coronary intervention (PPCI) or multivessel PCI, either during PPCI or as a staged procedure. Background MVD occurs in about 40% of patients presenting with STEMI, and it has been associated with a worse outcome compared to single‐vessel disease. The most favorable PCI strategy for dealing with significant nonculprit lesions has to be established. Methods A total of 2061 STEMI patients with MVD undergoing PPCI, prospectively enrolled in the REAL Registry between July 2002 and December 2010, were considered: 706 underwent culprit‐only PPCI; 367 multivessel PCI during the index procedure; 988 had a staged PCI within 60 days. Mortality and outcomes were calculated at 30 days and 2 years. Results At multivariate analysis, culprit‐only PPCI was associated with higher rates of cardiac outcomes as compared to staged multivessel PCI, taken as reference [Hazard Ratio (HR): 2.81, 95% confidence interval (CI): 1.34–5.89, P = 0.006 for 30‐day mortality, and HR: 1.93, 95% CI: 1.35–2.74, P = 0.0002 for 2‐year mortality, respectively]. Short‐term mortality rates were higher in multivessel PCI group as compared to staged PCI group (HR: 2.58, 95% CI: 1.06–6.26, P = 0.03); no differences were observed at 2‐year follow‐up (HR: 1.08, 95% CI: 0.64–1.82, P = 0.76). Conclusions Our findings support the current guidelines recommendation to perform culprit‐only PPCI in STEMI patients with MVD without hemodynamic compromise, followed by a staged PCI of noninfarct‐related significant lesions. © 2014 Wiley Periodicals, Inc.